Cognitive impairment and pain-related disability in patients with chronic pain: a mediation analysis - Alicja Timm; Frederick Junker; Sandra Blenk; Tobias Schmidt-Wilcke (PAIN Reports)
Abstract. Objectives:. Dyscognition is highly prevalent in patients with chronic pain and is thought to contribute to disability. The term “dyscognition” refers to cognitive complaints, which are primarily described as perceived deficits in concentration and memory, and cognitive impairments assessed by neuropsychological testing. This cross-sectional study investigated both aspects of dyscognition, with a specific interest in how these dimensions of dyscognition relate to disability. Methods:. The study enrolled 128 patients with chronic pain and 119 healthy control participants. Self-report questionnaires assessed pain intensity, pain catastrophizing, pain coping, fatigue, depression, and cognitive complaints. All patients and controls also underwent neuropsychological testing regarding attention and executive functioning, problem-solving, and episodic memory. In addition to group comparisons, we performed mediation analyses to investigate whether dyscognition may mediate the relationship between pain and pain-related disability. Results:. Patients with chronic pain extensively reported self-perceived cognitive deficits and showed performance-based cognitive impairments in executive functioning and problem-solving. Cognitive complaints and objective cognitive impairments were not correlated. Findings indicated that the impact of chronic pain on disability was mediated by emotional factors, specifically pain-related helplessness and depression, fatigue, and cognitive complaints, specifically hyperactivity and motor agitation, but not by cognitive impairment as assessed by neuropsychological testing. Conclusion:. Dyscognition, both self-reported concerns and impairments as assessed by neuropsychological testing, was highly prevalent in patients with chronic pain, with a significant impact on pain-related disability. Study findings suggest that dyscognition should be taken seriously in patients with chronic pain, especially when evaluating the impact of pain on activities and participation.